From Dickens to Dracula : Gothic, economics, and Victorian fiction - Houston, Gail Turley, 1950- (Cambridge, UK ; New York : Cambridge University Press, 2005)
Gail Turley Houston examines how the language and imagery of economics are transformed in Gothic fiction, and traces literary and uncanny elements in economic writings of the period. This stimulating interdisciplinary book reveals that the worlds of Victorian economics and Gothic fiction, seemingly separate, actually complemented and enriched each other.
Cover; Half-title; Title; Copyright; Dedication; Epigraph; Contents; Illustrations; Acknowledgments; Abbreviations; CHAPTER 1 Banking on panic: the historical record and a theoretical frame; CHAPTER 2 Gothic economies in Bagehot, Marx, and Lord Overstone; CHAPTER 3 The ghost and the accountant: investing in panic in Villette; CHAPTER 4 "The Whole Duty of Man": circulating circulation in Dickens's Little Dorrit; CHAPTER 5 "Bankruptcy at my heels": Dr. Jekyll, Mr. Hyde, and the bankerization of identity; CHAPTER 6 Bankerization panic and the corporate personality in Dracula; Notes; Index.
Includes bibliographical references (pages 132-157) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Dickens, Charles, -- 1812-1870 -- Knowledge -- Economics; Stoker, Bram, -- 1847-1912.; Dracula, -- Count (Fictitious character); Dickens, Charles, -- 1812-1870 -- Et l'aspect économique.; Stoker, Bram, -- 1847-1912; Dickens, Charles, -- 1812-1870; Dracula (Stoker, Bram); Dracula, -- Count (Fictitious character); English fiction -- 19th century -- History and criticism; Economics in literature; Economics and literature -- Great Britain -- History -- 19th century; Financial crises -- Great Britain -- History -- 19th century; Horror tales, English -- History and criticism; Gothic revival (Literature) -- Great Britain; Financial crises in literature; Money in literature; Dracula (Personnage fictif); Économie politique et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Roman anglais -- 19e siècle -- Histoire et critique; Économie politique dans la littérature.; Krach dans la littérature.; Argent dans la littérature.; Littérature frénétique -- Grande-Bretagne.; Récits d'horreur anglais -- Histoire et critique; Krachs -- Grande-Bretagne -- Historie -- 19e siècle.; Krachs -- Grande-Bretagne -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Economics; Economics and literature; Economics in literature; English fiction; Financial crises; Financial crises in literature; Gothic revival (Literature); Horror tales, English; Money in literature; Great Britain; Victoriaanse tijd; Gothic novel; 1800-1899; Electronic books; Criticism, interpretation, etc; History